Two trillion gallons: Fuel savings from fuel economy improvements to US light-duty vehicles, 1975–2018. (July 2020) - Greene, David L.; Sims, Charles B.; Muratori, Matteo
Abstract: Since 1975, the fuel economy of new light-duty vehicles sold in the U.S. has almost doubled. Fuel economy improvements on laboratory tests gradually became real improvements on the road as newer, more efficient vehicles replaced older less efficient ones. Fleet-wide fuel economy gains produced large fuel savings. In this paper, we show that fuel economy gains measured on laboratory test cycles, adjusted for on-road conditions and weighted by the distribution of vehicles by age and their relative use, closely match estimates by the Federal Highway Administration based primarily on traffic counts and motor fuel tax records. Adjusting for the rebound effect of fuel economy on vehicle miles traveled, we estimate the fuel savings, CO2 emissions reductions and dollars saved on fuel due to fuel economy improvements over the past 43 years. Through the end of 2018, estimated cumulative fuel savings amount to approximately 2 trillion gallons of gasoline. We estimate that roughly one-fifth of the savings can be attributed to gasoline price increases over the period and four-fifths to fuel economy and greenhouse gas (ghg) standards. Highlights: Fuel economy of new light-duty vehicles in the US almost doubled from 1975 to 2018. MPG gains on regulatory tests yielded proportional on-road improvements. This saved 2 trillion gallons of gasoline and 17 billion tonnes of CO2 . Fuel economy and ghg standards drove about 4/5 of the fuel savings. Indirect impacts, e.g. rebound effect, were relatively small.